Organic chemistry - Klein, David R. (Wiley, 2018)
"Organic chemistry is not merely a compilation of principles, but rather, it is a disciplined method of thought and analysis. Success in organic chemistry requires mastery in two core aspects: fundamental concepts and the skills needed to apply those concepts and solve problems. Readers must learn to become proficient at approaching new situations methodically, based on a repertoire of skills. These skills are vital for successful problem solving in organic chemistry. Existing textbooks provide extensive coverage of, the principles, but there is far less emphasis on the skills needed to actually solve problems"--